2017
DOI: 10.1007/s10549-017-4264-y
|View full text |Cite
|
Sign up to set email alerts
|

Abbreviated breast dynamic contrast-enhanced MR imaging for lesion detection and characterization: the experience of an Italian oncologic center

Abstract: Abbreviated approach to breast MRI examination reduces the image acquisition and the reading time associated with MR substantially without influencing the diagnostic accuracy (high sensitivity and NPV >99.5%). AP could translate into cost-savings and could enable a higher number of examinations within the same MR session.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…A shared finding in almost all abbreviated MRI studies is that the cancers detected were mainly early‐stage invasive cancers, with percentages ranging from 64–97%. The ductal carcinomas in situ (DCIS) detected with abbreviated MRI screening were predominately intermediate or high‐grade DCIS . This is in good agreement with a recent study by Sung et al, who found that in women at high breast cancer risk who underwent screening with both mammography and MRI, invasive cancers were more likely to be detected with MRI, while most cancers found with mammography were DCIS .…”
Section: Abbreviated Mrisupporting
confidence: 86%
See 2 more Smart Citations
“…A shared finding in almost all abbreviated MRI studies is that the cancers detected were mainly early‐stage invasive cancers, with percentages ranging from 64–97%. The ductal carcinomas in situ (DCIS) detected with abbreviated MRI screening were predominately intermediate or high‐grade DCIS . This is in good agreement with a recent study by Sung et al, who found that in women at high breast cancer risk who underwent screening with both mammography and MRI, invasive cancers were more likely to be detected with MRI, while most cancers found with mammography were DCIS .…”
Section: Abbreviated Mrisupporting
confidence: 86%
“…Whereas the above‐mentioned studies included T 2 ‐weighted or STIR sequences in their protocols, others solely relied on DCE‐MRI. Petrillo et al investigated an abbreviated protocol including one precontrast T 1 ‐weighted and the first postcontrast T 1 ‐weighted series in 508 patients, yielding similar results with comparable diagnostic accuracy of the abbreviated and the full protocols . Romeo et al used a protocol that included localizer, precontrast, and three timepoint postcontrast sequences to enable the assessment of the delayed enhancement.…”
Section: Abbreviated Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…However, high cost and lengthy exam time contributes to limited DCE-MRI utilization, even among women who meet criteria for high-risk screening (40,41). To decrease scan time, abbreviated MRI protocols have been explored with promising preliminary results (42,43). However, both DCE and abbreviated MRI protocols are dependent on the use of intravenous gadolinium, which accounts for additional cost and time associated with obtaining intravenous access and the gadolinium agent itself.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, contrast‐enhanced abbreviated breast MRI protocols consist of a localizer and a native as well as a single early postcontrast T 1 ‐weighted sequence . By subtracting the native from the enhanced scan, a subtraction mask is calculated that solely displays contrast‐enhancing areas .…”
Section: Contrast‐enhanced Abbreviated Mri Of the Breastmentioning
confidence: 99%